The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1080/00016480802179727
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the hearing results of KTP and Erbium YAG laser stapedotomy

Abstract: The study indicated that KTP and Er: YAG stapedotomies have similar rates of the air-bone gap closure. There was no significant postoperative sensorineural hearing loss found in both techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
(7 reference statements)
0
2
0
1
Order By: Relevance
“…Adequate randomization, treatment allocation, and blinding were either not achieved or no information was provided regarding these criteria. Standardization of treatment was unclear in 3 of the included studies (13,16,17). Laser settings were not adequately described in these studies.…”
Section: Retrieving Studiesmentioning
confidence: 99%
“…Adequate randomization, treatment allocation, and blinding were either not achieved or no information was provided regarding these criteria. Standardization of treatment was unclear in 3 of the included studies (13,16,17). Laser settings were not adequately described in these studies.…”
Section: Retrieving Studiesmentioning
confidence: 99%
“…Diese können vorübergehend sein oder persistieren. Andere Autoren befanden den Er:YAG-Laser jedoch als sicher [38,50].…”
Section: Diskussionunclassified
“…Due to a low absorption of energy in water both the argon and KTP laser have a high penetration depth within the perilymph and subsequently a theoretical risk of inner ear damage by a direct impact of laser energy ( 14 , 15 ). However, in the past several studies have demonstrated good postoperative results with no significant inner ear damage ( 16 18 ). Hence both, the argon and the KTP laser are widely used lasers for stapedotomy.…”
mentioning
confidence: 99%